2020
DOI: 10.1016/j.ijhydene.2020.06.194
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of hydrogen release in a naturally ventilated covered car park

Abstract: Highlights Hydrogen release from onboard storage in a covered car park is numerically investigated  Release and dispersions from a range of TPRD diameters is simulated  A 0.5 mm diameter TPRD was found to be inherently safer for 700 bar storage  The angle of TPRD release was shown to have implications for passenger egress  Results support the inherently safe design of hydrogen fuel cell vehicles *Highlights (for review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…The efficiency depends of course of the environmental operating conditions. In any case, this system permits to involve not more than a few per cent of the tank available energy which dramatically reduces the consequences of a catastrophic tank rupture [76,77]. To reinforce the FCV security, two projects are under study.…”
Section: H 2 Safetymentioning
confidence: 99%
“…The efficiency depends of course of the environmental operating conditions. In any case, this system permits to involve not more than a few per cent of the tank available energy which dramatically reduces the consequences of a catastrophic tank rupture [76,77]. To reinforce the FCV security, two projects are under study.…”
Section: H 2 Safetymentioning
confidence: 99%
“…CFD methods have also been performed to numerically evaluate the behavior of hydrogen dispersion so that emergency measures can be taken immediately to reduce the hydrogen concentration under a lower flammable limit (LFL) [22][23][24]. H. Hussein et al [25] numerically assessed the impact of various conditions by varying leakage orifice, direction, and angle of flammable hydrogen cloud. It was concluded that a larger orifice contributes to a massive flow rate, leading to a severe pressure-peaking phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Even unignited release from TPRD in a garage-like enclosure with limited vent size may lead to the pressure peaking phenomenon [4][5][6]. In a naturally ventilated covered car park, if there is no ignition, then understanding the release and dispersion of hydrogen and subsequent formation of a flammable cloud is the primary concern to define inherently safer conditions for TPRD release from passenger vehicles; this has been the focus of a previous study by the authors [7]. However, there is a need to understand how ignition impacts upon requirements for a safer release.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended by existing standards that the ventilation rate is such that in the case of hydrogen the concentration does not exceed 1% by volume i.e., 25% of the LFL within the car park; this is specified in ISO/DIS 19880-1 [12], NFPA 2 [13] and IEC (60079-10) [14]. This was the focus of previous work by the authors where an unignited release was considered within the same covered car park geometry presented here [7]. The British Standard BS 7346-7:2013 [15] defining the code of practice for underground car parks is used as a reference for the natural ventilation requirements in [7] and in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation